Slow Energy Transfer in Self‐Doped β‐Conformation Film of Steric Polydiarylfluorenes toward Stable Dual Deep‐Blue Amplified Spontaneous Emission. Issue 1 (18th October 2021) - Xu, Man; Sun, Lili; Wang, Shengjie; Lin, Jinyi; Yu, Mengna; Wang, Xuhua; Stavrinou, Paul N.; Xie, Linghai; Cheetham, Nathan J.; Ding, Xuehua; Bradley, Donal D. C.; Huang, Wei
Abstract: Exciton behavior is crucial for improving the optoelectronic property of a light‐emitting conjugated polymer. Herein, the photoexcitation dynamics of exciton migration and energy transfer in a self‐doped β‐conformation film of the polydiarylfluorenes (poly[4‐(octyloxy)‐9, 9‐diphenylfluoren‐2, 7‐diyl]‐co‐[5‐(octyloxy)‐9, 9‐ diphenylfluoren‐2, 7‐diyl], PODPF) are demonstrated. Compared to the first generation of the β‐conformation polyfluorene, poly(9, 9‐dioctylfluorene) (PFO), energy transfer occurs in PODPF β‐conformation films in a time period of ≈150 ps, much longer than those of the PFO ones (<5 ps), associated with the effective intrachain energy transfer (few hundred picoseconds), rather than interchain Förster energy transfer (a few picoseconds). Similar to PFO, the PODPF β‐conformation also displays well‐resolved vibronic emission peaks at 20 K, attributed to the planar and rigid conformation. Interestingly, a residual 0‐0 band emission of nonplanar conformation chain segments (435 nm, 2.85 eV) at 20 K also further confirms the exciton migration from the amorphous state to the β‐conformation domain in PODPF films. Therefore, the stable dual amplified spontaneous emission (ASE) behavior of the PODPF self‐doped films at 461 nm (2.69 eV) and 483 nm (2.57 eV), originates from the individual amorphous and β‐conformation domains. Abstract : Energy transfer occurs in β‐conformation polydiarylfluorenes films in a time period of ≈150 ps, longer than those of polydialkylfluorene (<5 ps), associated with the intrachain rather than interchain Förster energy transfer. Therefore, stable dual amplified spontaneous emission behavior is observed at 465 and 481 nm for self‐doped films, derived from the individual amorphous and β‐conformation chain segments.